This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: = x 2x 2 , l 1 ( x ) = ( x(1))( x1) (0(1))(01) = x 211 , l ( x ) = ( x(1))( x0) (1(1))(10) = x 2 + x 2 . The Simpson’s rule is derived as R S ( f ) = R 11 p 2 ( x )d x = f (1) R 11 l ( x )d x + f (0) R 11 l 1 ( x )d x + f (1) R 11 l 2 ( x )d x . 1 We have Z 11 l ( x )d x = Z 11 x 2x 2 d x = 1 2 ± x 3 3x 2 2 ² 11 = 1 3 , Z 11 l 1 ( x )d x = Z 11 x 211 d x =± x 3 3x ² 11 = 4 3 , Z 11 l 2 ( x )d x = Z 11 x 2 + x 2 d x = 1 2 ± x 3 3 + x 2 2 ² 11 = 1 3 . So Simpson’s rule for I ( f ) = R 11 f ( x )d x is R S ( f ) = 1 3 f (1) + 4 3 f (0) + 1 3 f (1). 2...
View
Full
Document
This homework help was uploaded on 04/07/2008 for the course MATH 3337 taught by Professor Xu during the Fall '07 term at Southern Methodist.
 Fall '07
 Xu
 Equations

Click to edit the document details